2004
DOI: 10.4141/p04-044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen, seeding date and cultivar on oat quality and yield in the eastern Canadian prairies

Abstract: . 2004. Effect of nitrogen, seeding date and cultivar on oat quality and yield in the eastern Canadian prairies. Can. J. Plant Sci. 84: 1025-1036. The proportion of oat (Avena sativa L.) being used for race horses and human consumption has increased over the past 15 yr. The objective of this study was to evaluate the effects of N, seeding date and cultivar on grain yield components, grain yield and grain quality of oat under a directseeding system. Four N rates, three seeding dates and two cultivars were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
56
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 22 publications
15
56
3
Order By: Relevance
“…Increasing rates of slurry-N did not have negative effects on test weight and kernel weight (Table 6) as was observed with increasing rates of inorganic fertilizer (May et al 2004a;Mohr et al 2007). Trials conducted by Brinkman and Rho (1984) demonstrated that oat grain yield superiority among cultivars in response to N was due to an increase in spikelets per panicle and weight per kernel across rates of N, rather than just the number of panicles per square metre.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Increasing rates of slurry-N did not have negative effects on test weight and kernel weight (Table 6) as was observed with increasing rates of inorganic fertilizer (May et al 2004a;Mohr et al 2007). Trials conducted by Brinkman and Rho (1984) demonstrated that oat grain yield superiority among cultivars in response to N was due to an increase in spikelets per panicle and weight per kernel across rates of N, rather than just the number of panicles per square metre.…”
Section: Discussionmentioning
confidence: 88%
“…Soil analysis services and the ''Nova Meter'' are available to cereal producers and commercial custom applicators to provide guidance in achieving targets for slurry application. Previous knowledge indicates that excess fertilizer N often results in yield reductions of oat (May et al 2004a;Mohr et al 2007). Agronomy trials have shown that swine slurry can be used as the sole source of fertilizer for cereal crop production if slurry is applied at the optimum rate and time using appropriate equipment (Petersen 1996;Mooleki et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations